Nabumetone and 6-MNA Pharmacokinetics, Assessment of Intrasubject Variability and Gender Effect - Světlík, Svatopluk; Štícha, Martin; Matoušková, Olga; Nespěšná, Lenka; Sklenář, Zbyněk; Bartůněk, Aleš; Perlík, František; Slanař, Ondřej (American journal of therapeutics, 2016)
In this open-label, laboratory-blinded, 2-way single dose study in 24 volunteers of both sexes we found that (1) nabumetone reaches mean Cmax ± SD of 0.56 ± 0.20 mg·L at mean tmax of 8.63 ± 7.05 hours, and mean area under the curve (AUC)last of 18.07 ± 7.19 h·mg·L; (2) there are no statistically significant differences between both sexes in pharmacokinetics of nabumetone; (3) 6-methoxy-2-naphthylacetic acid (6-MNA) reaches higher AUClast in men compared with women (mean ± SD, 721.23 ± 185.53 h·mg·L and 545.27 ± 97.69 h·mg·L, respectively; P = 0.013); (4) there is lower 6-MNA clearance in men (0.65 ± 0.22 L·h) in comparison with women (0.88 ± 0.18 L·h, P = 0.019), (5) intersubject variability of nabumetone and 6-MNA is between 35%-45% and 10%-30% for all assessed pharmacokinetics parameters (AUClast, Cmax, partial AUC values); (6) intrasubject variability (ISCV) for AUClast is low, 15.59% and 6.40% for nabumetone and 6-MNA, respectively, (7) ISCV for Cmax is 13.66% and 5.42% for nabumetone and 6-MNA, respectively. Nabumetone thus belongs to compounds with low to moderate ISCV and therefore this product is expected to produce consistent effects in clinical practice.
Keywords: dospělí; Female; kyseliny naftalenoctové; Butanones; Nabumetone; Adult; mladý dospělý; ženské pohlaví; Naphthaleneacetic Acids; lidé; Cyclooxygenase 2 Inhibitors; Area Under Curve; inhibitory cyklooxygenasy 2; butanony; Sex Factors; Male; sexuální faktory; Young Adult; plocha pod křivkou; mužské pohlaví; nabumeton; Humans